Trends in marketing library services in urban areas: A case study of selected libraries in Kampala City, Uganda - Kamosho, S. B.; Kigongo-Bukenya, I. M. N. (University of Dar es Salaam Library Journal, 2006)
This article presents the findings of a study that was undertaken in Kampala City, Uganda, in nine libraries belonging to the private sector, government, academic and diplomatic- related institutions. The aim of the study was to establish trends in marketing library services in urban areas with a view to identify marketing strategies of library services in Kampala City, and to establish the opportunities available and challenges that librarians encounter when marketing library services. Data was collected using questionnaires, interviews, focus group discussion , observation, and document content analyis. The study revealed that, overall, librarians in Kampala City appreciate the importance of marketing library services in the competitive information market. However, many librarians face challenges, among which is lack of marketing skills. The study recommends, amomng others, the retraining of library staff in marketing techniques